Challenges for transboundary river management in Eastern Europe – three case studies - Krengel, Fabian; Bernhofer, Christian; Chalov, Sergey; Efimov, Vasily; Efimova, Ludmila; Gorbachova, Liudmila; Habel, Michal; Helm, Björn; Kruhlov, Ivan; Nabyvanets, Yuri; et al. (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
The transboundary river basins shared between Russia, Ukraine and the European Union pose unique challenges for management because of differences regarding not only the legal framework but also related to monitoring practices and water utilization. Using the example of three river basins – the Desna (shared by Russia and Ukraine), the Western Dvina (shared by Russia, Belarus, Lithuania, Estonia and Latvia) and the Western Bug (shared by Ukraine, Belarus and Poland) – this paper provides an analysis of current challenges with respect to transboundary water resources management in Eastern Europe. This assessment is based on a comparison of similarities and disparities concerning the physical and human geography of the basins (and their national sub-basins) as well as specific problems related to water pollution caused by urban, agricultural and industrial water usage both in the recent past and today. All three catchments have a similar size, climate and hydrological characteristics. However, there are different challenges regarding up- and downstream sections of the respective basins: pollution input in the Western Bug originates primarily from upstream sources in Ukraine and Belarus, whereas ecological problems in the Desna and Western Dvina persist principally downstream, i.e. in Ukraine respectively Belarus and Latvia. Despite some differences between the basins, it is concluded that interstate cooperation is an important prerequisite for integrated water resources management (IWRM) in all of the studied basins. This analysis identified several key challenges related to start or continue with IWRM, including pollution mitigation, improved monitoring, appropriate governance, climate change and its effect on water balances in the catchments, capacity development and thorough system understanding.